2013
DOI: 10.1016/j.socscimed.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in travel time to radiotherapy facilities in the Atlanta metropolitan area

Abstract: Low-income women with breast cancer who rely on public transportation may have difficulty in completing recommended radiation therapy due to inadequate access to radiation facilities. Using a geographic information system (GIS) and network analysis we quantified spatial accessibility to radiation treatment facilities in the Atlanta, Georgia metropolitan area. We built a transportation network model that included all bus and rail routes and stops, system transfers and walk and wait times experienced by public t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…4951 This is consistent with our finding that blacks without Hispanic ethnicity and persons with Hispanic ethnicity had the highest death rate in the zone closest to a COG institution, Zone A, whereas death rates among whites without Hispanic ethnicity did not differ by zone. In contrast to these indicators of vulnerability are the relatively high median income and very high primary physician access in Zone A.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4951 This is consistent with our finding that blacks without Hispanic ethnicity and persons with Hispanic ethnicity had the highest death rate in the zone closest to a COG institution, Zone A, whereas death rates among whites without Hispanic ethnicity did not differ by zone. In contrast to these indicators of vulnerability are the relatively high median income and very high primary physician access in Zone A.…”
Section: Discussionsupporting
confidence: 90%
“…Public transportation, when available, adds considerably to the time and effort involved in accessing medical care. 4951 Moreover, access to specialist care can be hampered by lack of insurance or insurance that the specialist does not accept. 57,58 The net result in Zone A is a large population with a more limited attachment to the healthcare system than would be expected given the preponderance of primary physicians and the presence of COG institutions.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies have demonstrated, however, that radiation oncologists are geographically maldistributed across the nation, 7, 8 clustered at academic centers 7 and of limited accessibility relative to other oncology specialists. 9 Traveling long distances to cancer care is a barrier to cancer treatment, 1012 associated with decreased utilization of RT, 1315 or worse treatment outcome. 16 Even with data on association between geographic access and receipt of RT, there is limited information specific to rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main methods to delimit trade areas: the analogy method (Applebaum, 1965(Applebaum, , 1966Erickson and Finkler, 1985), the proximal area method (Okabe et al, 2008;Peipins, 2013;Guerrero and Kao, 2013) and the gravity method (Huff, 1963(Huff, , 1964. The analogy method is non-geographic and often implemented by regression analysis as first proposed by Applebaum (1965Applebaum ( , 1966.…”
Section: Delimiting the Health Service Areamentioning
confidence: 99%